PENGARUH BUDAYA HUKUM TERHADAP PEMBANGUNAN HUKUM GOOD GOVERNANCE DI INDONESIA - Sryani Br Ginting (IAIN Manado, 2016)
Constitutionally, rule of law is recognized in Indonesia. It means recognition of the law enforcement. Law is part of the community. Therefore, there is a term law community. The existence of law in Indonesia that can be encountered in daily life in the era of post-reform differs from that of the New Order (ORBA), either in positive or negative terms. Development continues to be implemented, as a process of change that is planned, to reach various aspects of the Indonesian community. One form of development is law development, which is also intrinsically related to other life aspects of similar social phenomena.In Indonesian society, where culture and social structure is complex, law serves more as a means of societal revival that grows from the community members who have power and authority, which may reflect the interests of the general public. Thus, the good governance project occurred, representing the Indonesian government's commitment to realize equitable and fair prosperity for all people, even for those in remote areas. This government effort led by the President, Mr. Joko Widodo, is not an easy task. President cannot work alone without cabinet ministers. The same is true for the central government. They cannot work without local government support. Therefore, the government cannot work without people or community participation in their endeavor to create an equitable and just society.The fundamental problem in Indonesia is a legal culture that has not operated well. Legal conditions that exist today are local and central authorities are being caught for bribery case, corruption, etc. When thought deeper, it appears that the Indonesian law culture is not good enough. Development in all aspects of life, it can be said, has not managed to produce good governance.Keywords: Legal culture, development of law, good governance.